Posyandu Cadres Education for HIV/AIDS Prevention and Transmission to Increase Cadre Knowledge on Women's Reproductive Health: Edukasi Kader Posyandu untuk Pencegahan dan Penularan HIV/AIDS untuk Meningkatkan Pengetahuan Kader pada Kesehatan Reproduksi Wanita - Nirma Lidia Sari (Yayasan Ahmar Cendekia Indonesia, 2023)
In Asia, Indonesia is the 5th most at risk of HIV/AIDS. Women are 2.5 times more susceptible to contracting HIV than men. Women's access to information and education affects the level of knowledge about reproductive health, including about HIV/AIDS. The role of cadres in preventing HIV/AIDS transmission to women in society is very important. This activity using counseling method and is intended as an effort to increase cadres' knowledge about HIV/AIDS. To assess the knowledge of the cadres, we use pretest and posttest. As the result, there are 10 cadres who joined this activity and the assessment test result shows that the knowledge of cadres are increase to 90% from none of cadres who get a good knowledge score. Counseling about HIV/AIDS can be useful to increase the knowledge of cadres. To continue the improvement of the cadres’ knowledge, stakeholders need to conduct periodic counseling and training on health education. Abstrak Di Asia, Indonesia menempati urutan ke-5 paling berisiko HIV/AIDS. Wanita 2,5 kali lebih rentan tertular HIV dibandingkan pria. Akses perempuan terhadap informasi dan pendidikan mempengaruhi tingkat pengetahuan tentang kesehatan reproduksi, termasuk tentang HIV/AIDS. Peran kader dalam pencegahan penularan HIV/AIDS pada perempuan di masyarakat sangat penting. Kegiatan ini menggunakan metode penyuluhan dan dimaksudkan sebagai upaya untuk meningkatkan pengetahuan kader tentang HIV/AIDS. Untuk menilai pengetahuan kader, kami menggunakan pretest dan posttest. Hasilnya, ada 10 kader yang mengikuti kegiatan ini dan hasil tes penilaian menunjukkan pengetahuan kader meningkat hingga 90% dari tidak ada kader yang mendapat nilai pengetahuan baik. Penyuluhan tentang HIV/AIDS dapat bermanfaat untuk menambah pengetahuan kader. Untuk melanjutkan peningkatan pengetahuan kader, pemangku kepentingan perlu melakukan penyuluhan dan pelatihan pendidikan kesehatan secara berkala.